Revision and phylogenetics of the genus Paraulax Kieffer (Hymenoptera, Cynipidae) with biological notes and description of a new tribe, a new genus, and five new species - Nieves-Aldrey, José Luis; Liljeblad, Johan; Nieves, María Hernández; Grez, Audrey; Nylander, Johan A. A. (Zootaxa, 2009)
The gall wasp genus Paraulax (Hymenoptera, Cynipidae) associated with southern beeches (Nothofagus (Nothofagaceae)) from South America is revised. The genus Paraulax and its type species, P. perplexa, are redescribed and a neotype is designated. Two additional species of Paraulax are described as new: P. queulensis and P. ronquisti. After having been first tentatively placed in the Cynipini and later transferred to the Pediaspidini, this genus is here placed in the newly erected tribe Paraulacini, together with the herein described genus Cecinothofagus and the three species that are described as new: C. gallaecoihue, C. gallaelenga and C. ibarrai. The biology of the members of this new tribe is discussed. Contrary to a prior hypothesis that postulated Paraulax (sensu lato) to be true gall-inducers, as most cynipids, evidence here shows that the three species of the new genus Cecinothofagus are instead parasitoids or lethal inquilines inhabiting galls induced by species of Aditrochus (Pteromalidae) on Nothofagus. The biology of the Paraulax species is unknown but since they too are associated with Nothofagus forests their biology is likely associated with the pteromalid gall community. We describe host plant associations as well as the morphology and phenology of the host gall. A phylogenetic reconstruction of the Paraulacini and selected Cynipidae taxa, based on 28S and COI, is performed. Both markers indicate the Paraulacini to be monophyletic and support a sister group relationship with the Pediaspidini. Results from 28S are congruent with both the morphological evidence and the proposed classification.